High Resolution Inverse Synthetic Aperture Radar Frequency Estimation using Fast Iterative Interpolated Beamformer - Parkinson, Jeremy; Ng, Brian (2023 IEEE International Radar Conference (RADAR), 2023)
This paper investigates the application of Fast Iterative Interpolated Beamformer (FIIB) to achieve high resolution Inverse Synthetic Aperture Radar (ISAR) images. FIIB is a low complexity frequency estimator which offers high levels of accuracy, making it suitable for ISAR Doppler processing. This study conducts simulations to evaluate the effectiveness of different frequency estimation techniques. FIIB is shown to produce highly focused images and outperforms the baseline Fast-Fourier-Transform (FFT) and MUltiple SIgnal Classification (MUSIC) algorithms across several metrics.